TALL-FORB COMMUNITIES OF THE NORTH ALTAI - ERMAKOV, N. (Annali di Botanica, 2003)
Classification of tall-forb vegetation of the Altai using the Braun-Blanquet approach was carried out on the basis of a wide ranging set o[ data from different altitudinal belts. Three main phytosociological types of the tall-forb communities were distinguished within the class MulgedioAconitetea, order Tmllio - Crepidetalia due to performed syntaxonomic analysis. The thermophilous tall-forb communities occurring in the subnemoral belt at altitudes of 259-700 m were included in the alliance Cacalio hastatae - Aconition septentrionalis all. nova. The montain tall-forb meadows of the dark-coniferous taiga belt (altitudes of 800-1700 m) were included in the alliance Triseto sibiricae-Aconirlon septentrionalis all. prov. The moderately cryophilous subalpine tall-forb communities widespread at the upper boundary of the forest belt at altitudes of 1000-1900 m were included in the alliance Rhaponticion carthamoidis. Altaian tall-forb vegetation shows a distinct phytosociological and plant geographical unity with European subalpine communities but the closeness of the floristic relations varies in certain altitudinal groups. Most thermophilous tall-forb Siberian meadows of the alliance Cacalio-Aconition which occur at lower altitudes demonstrate strong plant geographical relations with North and Central European meadows of the Adenostyletalia. Gradual decrease of the European floristic relations in the Altaian tall-forb meadows at higher altitudes is shown.